Rancang Bangun Aplikasi Pembelajaran dan Latihan Mengenal Abjad Berbasis Android Menggunakan Metode Pengembangan Design Thinking - Pranatawijaya, Viktor Handrianus; Putra, Rholand Deo Eka (Journal of Information Technology and Computer Science, 2022)
Kindergarten Education (TK) is a form of pre-school education that provides early education programs for children aged 4-5 years. And of course most of them use smartphone media as a means of playing. Based on these problems, we need a learning tool with smartphone media using the concept of learning while playing with UI/UX concepts that are attractive and easy to operate even for children aged 4-5 years though. Applications are designed and built using the Design Thinking development method, where this method focuses more on users who will run the application, in which there are 5 stages in the process, namely empathize, define, ideate, prototype, and test. From the results of calculating the effectiveness, efficiency and user satisfaction using the usability testing method and the system usability scale (SUS), it can be concluded that this application has been declared fit for use and can run well. So it can be said that this application can be a learning medium for children aged 4-5 years who still don't know or want to hone their knowledge of the A-Z alphabet.